Phylogenetic relationship and genomic characterization of Salmonella Typhimurium strains isolated from swine in Brazil - Seribelli, Amanda Aparecida; da Silva, Patrick [UNESP]; Frazão, Miliane Rodrigues; Kich, Jalusa Deon; Allard, Marc W.; Falcão, Juliana Pfrimer (Elsevier, 2021)
Salmonella Typhimurium has been transmitted between humans and animals. Although, Brazil has been one of the largest pork meat exporters worldwide, there are few studies that characterized epidemiologically S. Typhimurium strains from swine. The aims of this work were to study the phylogenetic relationship of S. Typhimurium genomes isolated from swine in Brazil among themselves and with other genomes isolated from several sources and countries using wgMLST and cgMLST and to perform the search of Salmonella pathogenicity islands (SPIs). In addition, for S. Typhimurium strains from swine to compare the virulence and antimicrobial resistance genes by VFDB and ResFinder, genetic content by BLAST Atlas and orthologous proteins clusters by OrthoVenn. The constructed phylogenetic trees by wgMLST and cgMLST grouped the majority (92.3% and 80.7%, respectively) of the strains isolated from swine in Brazil into the same group. All the isolates contained important SPIs (SPI-1, SPI-2, SPI-3, SPI-5 and SPI-9). A total of 100 and 31 virulence and resistance genes were detected in the S. Typhimurium strains isolated from swine, respectively. The BLAST Atlas and orthologous proteins analysis found regions of phages and differences in metabolic, regulatory and cellular processes among S. Typhimurium LT2 and S. Typhimurium isolates from swine. In conclusion, molecular typing based in the wgMLST and cgMLST suggested that the S. Typhimurium isolates from swine studied were genetically related. The pathogenic potential of the strains studied was corroborated by the presence of important SPIs and virulence genes. The high number of antimicrobial resistance genes detected is worrying and reinforced their potential risk in swine in Brazil. The comparison by BLAST Atlas suggested differences in mobile genetic elements among S. Typhimurium LT2 and S. Typhimurium isolates from swine in Brazil. The orthologous proteins analysis revealed unique genes related to important cellular processes in the strains from swine.
Keywords: BLAST Atlas; Orthologous proteins; Phylogenetic analyses; SPIs; Virulence and resistance genes